Comparison of Javanese lexicon in Banyumas and Banyuwangi dialect bilingual dictionaries - Darmawan, Muhamad Rizki; Budiono, Satwiko (citeus, 2025)
The Banyumas and Banyuwangi dialects of Javanese exhibit notable lexical similarities, particularly in their retention of Old Javanese vocabulary, consonant endings, the specificity of vowel phonemes, and syllabic structures. These linguistic commonalities necessitate further research at other linguistic levels to substantiate the similarities between these two geographically distant dialects. This comparison also serves as a basis for reinforcing the hypothesis of a historical migration of Javanese speakers from Banyumas to Banyuwangi. Furthermore, this study confirms that the varieties of Javanese spoken in Banyumas and Banyuwangi constitute distinct dialects. This study employs a mixed-methods approach, integrating both quantitative and qualitative methodologies to increase the robustness of its findings and avoid potential biases. In other words, mixed methods make research more objective and comprehensive. Data was collected using a corpus linguistic framework using the AntConc application. Primary data sources included two bilingual dictionaries: Banyumasan—Indonesian Javanese Dictionary and the Using-Indonesia Regional Language Dictionary. The analysis—grounded in lexical semantics and dictionary microstructure in lexicology—reveals that the lexicons in the two dictionaries have similar lemma forms, similar and different classes, and similar semantic features. The similarity of the lemma forms is influenced by the standard Javanese dialect. Quantitative analysis indicates that 32% of the lexicons in both dictionaries are identical, whereas 68% differ. These findings confirm that despite their shared linguistic elements, the Banyumas and Banyuwangi varieties constitute distinct dialects of Javanese, though neither deviates significantly from the standard dialect.